Profile Of Antiretroviral Side Effects On Hiv In Rspi Prof. Dr. Sulianti Saroso Jakarta - Yelfi Anwar; Sucahyo Adi Nugroho; Sri Dwi Wulandari (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Symptoms of Acquired Immuno Deficiency Syindrome (AIDS) is a militia or disease caused by me infection of Human Immunodeficiency immune deficiency due to Antiretroviral. Due to Virus (HIV). The therapy used is a drug that the use of Antretroviral is the appearance of unwanted reactions or side effects will appear. The objectives of the study were to analyze the side effects of antiretroviral therapy in HIV / AIDS patients in RSPI Sulianti Saroso, North Jakarta, January-June 2016 period. The sample was 95 patients. The research was done by retrospective method, data analysis desknptif data presented in tabular form and presented with pie chart. The result of the research is the combination of TDF + 3TC + Efavirenz Tenofovir-Lamivudin-Efavirenz) as much as 73,68% (0 person). There were 94.73% (90 people had mild adverse reactions and 5.27% (5 people) severe side effects.